Coupled model for grain rotation, dislocation plasticity and grain boundary sliding in fine-grained solids. (November 2020) - Borodin, E.N.; Mayer, A.E.; Gutkin, M.Yu.
Abstract: Based on a new model coupling both direct and inverse grain rotation processes, we discuss interrelations between the dislocation mechanism of plasticity and the grain boundary sliding in fine-grained solids. The high-strain-rate deformation conditions, corresponding to molecular dynamics simulations, and processes of severe plastic deformation are in the focus of our consideration. The model correctly predicts the transition point below which the shape of nanograins remains equiaxed after deformation. For nanocrystalline copper, it corresponds to grains of several nanometers in size, while for ultrafine-grained copper – some hundreds of nanometers, that is in a good agreement with experimental data. A consequence from the existence of two transition points is the presence of grain size range between these points where the grains remain distorted after deformation. Our calculations show that for copper, this range is from 6 to 20 nm. The model also predicts the existence of a limit strain rate above which grains cannot be equiaxed. For this strain rate, our calculations give tens of inverse seconds for nanocrystalline copper and a few inverse seconds for ultrafine-grained one. Highlights: The interrelation of dislocation plasticity and grain boundary sliding is discussed. There are two transitional grain sizes below which grains remain equiaxed. In the range of grain sizes from 6 to 20 nm distorted grains in copper are expected. Copper grains cannot be equiaxed at strain rates above tens of inverse seconds.